Counseling service in overcoming faith and morality issues for inmates child - Fadila Fadila; Beni Azwar; Hartini Hartini (Indonesian Institute for Counseling, Education and Therapy (IICET), 2020)
According to the Directorate General of Corrections, more than 7,000 children perpetrate criminal offenses on a yearly basis. To reduce this crime rate, it is of great necessity to reinforce Religion, values, and morals (RNM) through appropriate counseling services to inmates child at the Rejang Lebong Class II A Curup Correctional Institution. The solution to the problem in this study is first, improving the condition of religion, the values, and morals of the child. Second, the type of counseling assignment in terms of Religion, Values, and Morals of the children faced with the law. Third, the condition of religion, the values and morals of the children who became upright after counseling services is given. This research is based on the grounded theory which has to do with building a theory through inductive studies. His observations are illustrated by the results of the 87% of inmates child themed test problem in ANM. He was given personal guidance for the development of religious life in the areas of information services, content mastery services, group guidance services, and individual counseling. At the test post, there was a decrease of 43% in the inmates child ANM problems.